2017
DOI: 10.1073/pnas.1700678114
|View full text |Cite
|
Sign up to set email alerts
|

Triad of human cellular proteins, IRF2, FAM111A, and RFC3, restrict replication of orthopoxvirus SPI-1 host-range mutants

Abstract: Viruses and their hosts can reach balanced states of evolution ensuring mutual survival, which makes it difficult to appreciate the underlying dynamics. To uncover hidden interactions, virus mutants that have lost defense genes may be used. Deletion of the gene that encodes serine protease inhibitor 1 (SPI-1) of rabbitpox virus and vaccinia virus, two closely related orthopoxviruses, prevents their efficient replication in human cells, whereas certain other mammalian cells remain fully permissive. Our highthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 54 publications
3
51
0
Order By: Relevance
“…Supporting this idea, an unbiased FAM111A interactome analysis revealed the Replication Factor C (RFC) complex, the main cellular PCNA loader 8 , but not PCNA itself as a major replication fork-associated cellular FAM111A binding partner ( Fig. 1h), in agreement with genetic data indicating a link between FAM111A and RFC subunits in restricting viral replication 9 . Co-immunoprecipitation experiments suggested that FAM111A associates with the RFC complex through interaction with the RFC1 subunit independently of the PIP box, involving a region of the extended regulatory N-terminal portion of human RFC1 that encompasses its BRCT domain 8 (Fig.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Supporting this idea, an unbiased FAM111A interactome analysis revealed the Replication Factor C (RFC) complex, the main cellular PCNA loader 8 , but not PCNA itself as a major replication fork-associated cellular FAM111A binding partner ( Fig. 1h), in agreement with genetic data indicating a link between FAM111A and RFC subunits in restricting viral replication 9 . Co-immunoprecipitation experiments suggested that FAM111A associates with the RFC complex through interaction with the RFC1 subunit independently of the PIP box, involving a region of the extended regulatory N-terminal portion of human RFC1 that encompasses its BRCT domain 8 (Fig.…”
supporting
confidence: 75%
“…Although both RFC1 and RPB1 emerge as attractive candidate FAM111 substrates based on our findings, we have so far been unable to conclusively establish such relationships. While the biological functions of FAM111 proteases are not well understood, our finding that FAM111 proteolytic activity is dispensable for normal cell growth but powerfully suppresses DNA replication, transcription and cell viability once elevated is well aligned with the putative role of FAM111A as a host restriction factor suppressing Simian Virus 40 (SV40) and poxvirus gene expression and DNA replication 5,6,9 . When properly controlled, these features could provide an important contribution towards a general line of defense against invading viruses and their propagation.…”
mentioning
confidence: 66%
“…However, the VACV proteins A20 and D4 form a complex with the VACV DNA polymerase to provide a similar function (18). Nevertheless, a possible role for PCNA in replication of VACV was suggested indirectly by a report that two human PCNA-associated proteins are inhibitors of a host range mutant (104). To ascertain whether to pursue this lead in the future, we investigated the effect of the specific PCNA inhibitor T2AA (105).…”
Section: Discussionmentioning
confidence: 99%
“…RNAi screening was conducted using the Ambion Silencer® Select Human Druggable Genome siRNA Library Version 4 as described previously [63] and the HTRF assay for NS1 antigen was performed as described above. The HTRF signal was for each unique non-overlapping siRNA against the target genes was normalized to a negative control targeting siRNA.…”
Section: Sirna Screeningmentioning
confidence: 99%